2021
DOI: 10.1111/jir.12883
|View full text |Cite
|
Sign up to set email alerts
|

Association between physical fitness, body mass index and intelligence quotient in individuals with intellectual disabilities

Abstract: Background Physical exercise seems to improve cognitive abilities at different physiological levels. Numerous studies have examined the relationship between physical fitness (PF), physical activity and cognition among populations without intellectual disabilities (ID), but very few have addressed this question with respect to people with ID. This study aimed to determine the correlation between intelligence quotient (IQ) and factors related to PF in healthy adults with ID. Methods A multicentre cross-sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…On the other hand, a low balance has been associated with the peripheral sensory deficits often experienced by these individuals, especially those referring to the somatosensory, visual, and vestibular systems (Blomqvist et al, 2013; Leyssens et al, 2022). Other factors could contribute to these deficits, including (i) age, a factor that is aggravated by the premature aging that characterises this group (Enkelaar et al, 2012), (ii) impairment of higher cognitive functions (Cabeza‐Ruiz et al, 2021), (iii) obesity and lack of physical activity, which are linked to the barriers to access physical activity (Guidetti et al, 2010), and (iv) challenging behaviour, associated with communication difficulties and sedentary lifestyle (Nankervis et al, 2020). In addition, it has been reported that women with intellectual disabilities have a higher body mass index and twice the probability of suffering from obesity than their male peers (Barnes et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, a low balance has been associated with the peripheral sensory deficits often experienced by these individuals, especially those referring to the somatosensory, visual, and vestibular systems (Blomqvist et al, 2013; Leyssens et al, 2022). Other factors could contribute to these deficits, including (i) age, a factor that is aggravated by the premature aging that characterises this group (Enkelaar et al, 2012), (ii) impairment of higher cognitive functions (Cabeza‐Ruiz et al, 2021), (iii) obesity and lack of physical activity, which are linked to the barriers to access physical activity (Guidetti et al, 2010), and (iv) challenging behaviour, associated with communication difficulties and sedentary lifestyle (Nankervis et al, 2020). In addition, it has been reported that women with intellectual disabilities have a higher body mass index and twice the probability of suffering from obesity than their male peers (Barnes et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Force and balance have been proposed as the two most sensitive indicators of the physical condition in people with intellectual disabilities (Cabeza‐Ruiz et al, 2021; Cuesta‐Vargas et al, 2022; Delgado‐Lobete et al, 2021; Leyssens et al, 2022; Oppewal & Hilgenkamp, 2018). This is further supported by the fact that most intervention programs aimed at improving the physical fitness of people with intellectual disabilities considered both strength and balance training.…”
Section: Introductionmentioning
confidence: 99%